2021
DOI: 10.1101/2021.01.26.21250511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The angiotensin type 2 receptor agonist C21 restores respiratory function in COVID19 - a double-blind, randomized, placebo-controlled Phase 2 trial

Abstract: BackgroundAlthough several therapies have been evaluated for treatment of COVID-19, the morbidity and mortality in COVID-19 are still significant, and the need for safe and effective drugs remains high even after launch of vaccine programs.MethodsWe conducted a double-blind, randomized, placebo-controlled trial with the novel oral angiotensin II type 2 receptor agonist C21 in hospitalized COVID-19 patients with C-reactive protein 50-150 mg/L but not needing mechanical ventilation. Patients were randomly assign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Restoring RAS balance could be achieved through many means, including injections of soluble human recombinant ACE2 [ 19 ], AT2R activators [ 68 ], AT1R blockers (ARBs) [ 65 ] or angiotensin converting enzyme inhibitors (ACEIs) [ 67 ]. Accordingly, an agonist of AT2R improves respiratory functions and reduces mortality in COVID-19 patients [ 74 ]. Similarly, it has been recently shown that the treatment with ACEIs or ARBs during COVID-19 hospitalization reduces mortality [ 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Restoring RAS balance could be achieved through many means, including injections of soluble human recombinant ACE2 [ 19 ], AT2R activators [ 68 ], AT1R blockers (ARBs) [ 65 ] or angiotensin converting enzyme inhibitors (ACEIs) [ 67 ]. Accordingly, an agonist of AT2R improves respiratory functions and reduces mortality in COVID-19 patients [ 74 ]. Similarly, it has been recently shown that the treatment with ACEIs or ARBs during COVID-19 hospitalization reduces mortality [ 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Instead of increasing ACE2, selective AT1R antagonism by ARBs has been hypothesized to aid in ameliorating lung pathology in COVID-19 through rebalancing Ang II/angiotensin (1-7) ratio and indirectly promoting Ang II-induced activation of AT2R with antagonistic effect against Ang II activation of AT1R [34,40]. A recent small randomized clinical trial showed that C21, an agonist of AT2R, could improve mortality rate and respiratory function significantly in hospitalized patients with COVID-19 [41]. However, the use of ARBs was constrained in the early phase of the pandemic due to concerns over their possible role in increasing viral load due to ACE2upregulating effect of these drugs [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…After abstract screening and full-text reading, 152 RCTs were included in the analysis. All 152 RCTs were posted on the medRxiv server …”
Section: Resultsmentioning
confidence: 99%